Applying Microsoft Office 365 in learning Islamic Education (PAI) amid Covid-19 Pandemic - Ali Akbar; Nurul Fajri (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
Distance learning is the right choice during Covid 19 pandemic. Because of this reason, an appropriate application is needed to support the distance learning process. The purpose of this study was to describe the use of Microsoft Office 365 as an instructional media in learning PAI virtually. This was a case study research which used observation and interview techniques to collect the data. Data were analyzed thematically by reducing, displaying, and concluding data. The result of the study described that Microsoft Office 365 could be used by teachers as an instructional media of online learning during Covid 19 pandemic. The available features could support virtual learning system and optimized the process of distance learning. Therefore, students could learn well during pandemic.Â Â